SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA LKP REJEKI CILACAP - Chandra Kesuma; Desiana Nur Kholifah (Universitas Bina Sarana Informatika, 2019)
Abstract - Academic information systems still use the manual way processing value still use writing hand and the announcement of academic and notice the other students coming to LKP. It leads to academic web based information system allowing students to get academic information don’t need to visit LKP and more practical without taking the time to education authorities. Inside this web academic information system management is divided into 4 user is admin, teachers, students, and visitors. Users are given certain privileges, admin access rights granted in the form of overall management ranging from the management of student data input, the data value of students, teacher’s data, academic information will be informed on academic news. Then teachers are given permission to enter the data value of students, and general information about the schedule and updoad academic like material, and students can only access the data of personal values, as well as information such as schedules and academic news material. This website only informs about the daily assessment, the value of the task, the value of UTS, UAS, the result value, and certificates. We make online system can achieve an activity that is effective in supporting the activities of LKP more favorable compared with the manual system.Keywords: Information Systems, Academic, Web, Processing Value, ValueAbstrak - Sistem informasi akademik yang masih manual yaitu pengolahan nilai masih menggunakan tulis tangan serta pemberitahuan nilai dan pengumuman akademik lainnya peserta didik harus datang ke LKP. Untuk itu dibuatlah sistem informasi akademik yang berbasis websehingga peserta didik yang ingin mendapatkan informasi akademik tidak lagi datang ke LKP dan lebih praktis tanpa meluangkan waktu ke instansi pendidikan tersebut. Di dalam web ini Pengelolaan sistem informasi akademik terbagi kedalam 4 pengguna yaitu admin, guru, siswa, dan pengunjung. User diberikan hak akses tertentu, admin diberikan hak akses berupa pengelolaan secara keseluruhan mulai dari pengelolaan input data siswa, data nilai, data guru, informasi akademik yang akan diinformasikan pada berita akademik. Kemudian guru diberikan hak akses untuk memasukkan data nilai siswa, dan informasi umum seputar akademik seperti jadwal dan updoad materi, dan siswa hanya bisa mengakses data nilai pribadi, serta informasi berita akademik seperti jadwal dan materi. Website ini hanya menginformasikan tentang penilaian harian, nilai tugas, nilai UTS, UAS, hasil nilai, dan sertifikat. Dengan dibuatnya sistem secara online dapat tercapai suatu kegiatan yang efektif dalam menunjang aktifitas LKP yang lebih kondusif dibandingkan dengan sistem manual.Kata Kunci: Sistem Informasi, Akademik, Web, Pengolahan Nilai, Nilai